Immunological tolerance to LCMV antigens differently affects control of acute and chronic virus infection in mice. Issue 1 (15th September 2017) - Woopen, Christina; Straub, Tobias; Schweier, Oliver; Aichele, Ulrike; Düker, Katharina; Boehm, Thomas; Pircher, Hanspeter
Abstract: Cytotoxic T lymphocytes (CTLs) play a key role in the control of lymphocytic choriomeningitis virus (LCMV) infection. In C57BL/6 mice (H‐2 b ), the CTL response is mainly directed against epitopes from the LCMV glycoprotein (GP) and the nucleoprotein (NP) which represent the two major viral proteins. The role of GP‐ versus NP‐derived epitopes for viral clearance was examined using transgenic (tg) mice ubiquitously expressing LCMV GP and NP, respectively. These mice lack GP‐ or NP‐specific CTLs and show decreased levels of GP‐ or NP‐specific antibodies as a result of tolerance induction. During acute LCMV infection, CTLs specific for GP‐ and NP‐derived epitopes are generated with similar frequencies. Nonetheless, we found that lack of GP‐ but not of NP‐specific CTLs abolished control of acute LCMV infection. In contrast, after high‐dose or chronic LCMV infection, virus elimination was delayed to a similar extent in GP‐ and NP‐tg mice. Thus, immunological tolerance to LCMV antigens differently affects virus clearance in acute and chronic infection settings. In addition, our data reveal that immunodominance of H‐2 b ‐restricted LCMV‐specific CTL epitopes and their antiviral activity do not strictly correlate. Abstract : The role of LCMV glycoprotein (GP) versus nucleoprotein (NP) ‐derived epitopes for viral clearance was examined in LCMV antigen transgenic mice. Immunological tolerance to GP but not to NP abolished control of acute LCMV infection. In contrast, virus elimination was delayed to a similar extent in GP‐ and NP‐transgenic mice after chronic LCMV infection.